Targeting beta-lactamase activity with Oxacyclohexadecan-2-one in carbapenem-resistant uropathogenic E. coli: A molecular simulation approach - Priyanka Balaji; Madhana Priya N; Emmanuel Bhaskar M.; Gnanasambandan R; Solomon F. D. Paul; Magesh R. (PLoS ONE, 2025)
Urinary tract infections caused by uropathogenic Escherichia coli (E. coli) are a global health concern, with rising rates and antibiotic resistance demanding novel treatments. Therefore, in this study, we explored the potential of Oxacyclohexadecan-2-one obtained from Moringa oleifera (M. oleifera) seed, as antibacterial agent against three majorly prevalent carbapenemase-producing E. coli proteins, blaNDM-1 (New Delhi metallo-betalactamase-1), blaNDM-5 (New Delhi metallo-betalactamase-5) and blaOXA-48 (Oxacillinase-48) from the strains Ecw3, EC-114 and T20 respectively. The ethanolic extract of M. oleifera seed was subjected to GC-MS, identifying 135 compounds. PyRx virtual screening, identified the top 10 ligands for each protein following the Rule of 5 and ProTox classes V and VI, with Oxacyclohexadecan-2-one (PubChem ID: 235414) showing best binding affinity across all 3 proteins with an optimized dose (LD50) of 5000mg/kg. Hence, molecular docking was carried out for ligand 235414 along with Imipenem, belonging to the same class V toxicity class with an optimized dose (LD50) of 5000mg/kg. Imipenem is a commonly used FDA drug to treat UTIs, which served as the control in the study. Oxacyclohexadecan-2-one showed higher binding affinity for the beta-lactamase proteins with a docking score of -6.45 kcal/mol, -6.05 kcal/mol and -7.34 kcal/mol compared to -3.41 kcal/mol, -3.99 kcal/mol and -6.36 kcal/mol of Imipenem for NDM-1, NDM-5 and OXA-48 respectively. Dynamic Simulation was performed for 100 ns for Oxacyclohexadecan-2-one and Imipenem bound protein complexes to determine the stability, fluctuations, compactness, bond interaction, solvent accessibility area, free energy landscape and the binding free energy. The results of molecular docking and dynamics were promising for the Oxacyclohexadecan-2-one, suggesting its potent inhibitory effect against the beta-lactamase producing proteins.